2015
DOI: 10.1590/s0034-8910.2015049005438
|View full text |Cite
|
Sign up to set email alerts
|

Weather parameters and nosocomial bloodstream infection: a case-referent study

Abstract: OBJECTIVE To evaluate if temperature and humidity influenced the etiology of bloodstream infections in a hospital from 2005 to 2010.METHODS The study had a case-referent design. Individual cases of bloodstream infections caused by specific groups or pathogens were compared with several references. In the first analysis, average temperature and humidity values for the seven days preceding collection of blood cultures were compared with an overall “seven-days moving average” for the study period. The second anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
1
2
0
4
Order By: Relevance
“…Second, we observed seasonal or temperature variations in the incidence of ABI and ABP in China, consistent with previous reports in other countries [32][33][34]. This may be the Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Second, we observed seasonal or temperature variations in the incidence of ABI and ABP in China, consistent with previous reports in other countries [32][33][34]. This may be the Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Acinetobacter was found in high incidence (24% of all infected patients) [40]. One study found an increased incidence of gram-positive organisms [47] while the Sepsis Occurrence in Acutely Ill Patients (SOAP) study reported an equal frequency of gram-positive and gram-negative organisms [28]. In a study done by Vincent et al, 2006 [28], Acinetobacter was involved in 9% of all infected patients, which was similar to the rate reported in EPIC study 1996 [48].…”
Section: Discussionmentioning
confidence: 99%
“…temperatura se relaciónó positivamente con la recuperación de los bacilos gram-negativos o Acinetobacter baumannii, incluso después del ajuste demográfico y los datos de admisión. Se identificó una relación inversa con la humedad (89).…”
Section: Resultados Por Grupos De Enfermedadesunclassified
“…• Es necesario establecer las enfermedades prioritarias para análisis de la relación de clima y salud en Colombia, dada la complejidad del tema y las series de tiempo a analizar. • Es necesario identificar las series de tiempo con las cuales cuentan los diferentes eventos en vigilancia para realizar los estudios pertinentes en el país del crecimiento bacteriano en reservorios inanimados (89).…”
Section: Recomendacionesunclassified